Temporal dynamics of animacy categorization in the brain of patients with mild cognitive impairment - Hamed Karimi; Haniyeh Marefat; Mahdiyeh Khanbagi; Chris Kalafatis; Mohammad Hadi Modarres; Zahra Vahabi; Seyed-Mahdi Khaligh-Razavi (PLoS ONE, 2022)
Electroencephalography (EEG) has been commonly used to measure brain alterations in Alzheimer’s Disease (AD). However, reported changes are limited to those obtained from using univariate measures, including activation level and frequency bands. To look beyond the activation level, we used multivariate pattern analysis (MVPA) to extract patterns of information from EEG responses to images in an animacy categorization task. Comparing healthy controls (HC) with patients with mild cognitive impairment (MCI), we found that the neural speed of animacy information processing is decreased in MCI patients. Moreover, we found critical time-points during which the representational pattern of animacy for MCI patients was significantly discriminable from that of HC, while the activation level remained unchanged. Together, these results suggest that the speed and pattern of animacy information processing provide clinically useful information as a potential biomarker for detecting early changes in MCI and AD patients.